Ring-expansion of an Aziridinone to a Hexahydrotriazine Through the Agency of a Novel Rearrangement - M. M., Yusoff; Talaty, Erach R (Elsevier, 1996)
Reaction of 1,3-di-t,'rt-bu~.laziridinonc (la) and similar aziridinones with thiosemicarbazide affords, as one of the products, a compound devoid of sulfur, vie., a substituted N- aminoimidazolidinone (3a) by selective cleavage of the acyl-nitrogcn bond. Compound 3a undergoes a novel, acid-catalyzed rearrangement to a 3-imino-hexahydro-1,2,4-tri~in-6-one (7a), which can also be obtained ~' treatment of la with hydrazinc followed by BrCN. involving again selective cleavage of the acyl-nitrogen bond.